Acute, subchronic, and chronic toxicity testing - Ruppert, Gregory (Henry Stewart Talks, 2012)
Purpose of acute, subchronic, and chronic general toxicology testing, Regulations and guidelines on conduct, Considerations and components to consider during study design, Differences between small and large molecule toxicology study designs
Reviewed at 2022/04/12